Random field modeling of reinforced retaining walls. Issue 3 (5th June 2015) - Dodagoudar, G.; Sayed, S.; Rajagopal, K.
<x content-type="archive" xml:space="preserve">Abstract</x> Conventional finite element method (FEM) relies on deterministic values to represent structural and load parameters and it does not have the capability of considering random parameters in response evaluation of the structures. In the context of stochastic computational mechanics, uncertainty modeling using random finite element method (RFEM) has by far received the major attention in recent years. The objective of the paper is to develop a computer program for stochastic analysis of reinforced retaining walls considering serviceability limit-state. The paper presents the formulation of the RFEM for random field modeling of the reinforced retaining walls. The developed program is validated using 1D bar and 2D plane-stress problems that involve random material properties. The random field is simulated by Cholesky decomposition of the covariance matrix. The Monte Carlo simulation (MCS) technique has been used in the finite element solution of the deformation response variability of the reinforced soil retaining wall. Results of the random finite element analysis are useful for serviceability limit-state design of the reinforced retaining walls.